FILTRASI AIR SEDERHANA DENGAN METODE SLOW SAND FILTER UNTUK MEMPERBAIKI KUALITAS AIR SAMBUNGAN RUMAH MASYARAKAT SEKITAR SEI MERDEKA SAMBOJA KABUPATEN KUTAI KARTANEGARA (Universitas Esa Unggul, 2022)
This research was conducted to help the community due to clean water problems in a simple and easy way. This research found a problem related to clean water in Sungai Merdeka Village, Samboja District, Kutai Kartanegara Regency, East Kalimantan Province. The problem experienced by the surrounding community is that the clean water that comes out of the house connection faucet cannot be used directly for cooking and drinking, but is only used for washing clothes, bathing and washing cutlery. People have consumed this water, but what happens is an uncomfortable feeling in the throat (inflammation) and when it use for bathing, it makes skin sometimes feels dry and tight. This is the reason to develop our research activities to find out how the condition of the water used by the community to fulfill their daily activities, to test the content of tap water in one of the residents' house. The efforts made to improve the quality of the Merdeka River community's tap water are by using Simple Filtration with the Slow Sand Filter principle, which is a filtering method that flows from the bottom up using several natural filter media without using chemicals. The media used include filter foam, silica sand, zeolite stone, activated carbon, palm fiber, and gauze nets. The pH value in residents' water faucets, which range from 4-6, that is not in requirements for clean water/drinking water issued by Permenkes no. 492 of 2010 which requires a pH value between 6.5 – 8.5. When compared to the pH value in the raw water source, namely the Merdeka River, it is even better, ranging from 5.6 to 6.4. The simple tool design was made, which namely Filtration with an upflow flow system (from bottom to top). The result is that after the residents' tap water is filtered through simple filtration, the air pH value becomes normal around 6.9 – 7.4. This means that the water meets the requirements set by the government according to the Minister of Health.